Open Government Implementation during the Pandemic: Lesson – Learned from Surakarta City Government - Nugroho, Rino Ardian; Dihandiska, Apneta Vionuke; Prakoso, Septyanto Galan; Putra, Ferdian Ahya Al (Political Science Program, Universitas Negeri Semarang, 2023)
Open government initiative is needed to ensure good governance by providing more transparent, innovative, collaborative, and participatory services to fulfill public needs. The need for open government is becoming higher during Covid-19 pandemic. The government of Surakarta city also experienced this situation as part of minimizing the impact of Covid-19 spread, by utilizing social media. The purpose of this study measures the open government maturity in Surakarta City Government during the early stage of the Covid-19 pandemic. The output of this study could be useful to hinder the spread of misinformation and disinformation in the pandemic situation that may reoccur in the future. The finding of this study is also useful as an example case of the implementation of open government during critical times. This research design uses qualitative descriptive methods and the analysis will be based on the Open Government Implementation Model (OGIM), by matching the current performance of Surakarta city government with the stages on OGIM. The result indicated that during the Covid-19 pandemic, Surakarta City Government has reached stage four of OGIM. The pandemic does not hinder the Surakarta City Government in providing openness to the public. The novelty of this study lies in the focus of analysis of open government implementation in a city level during the pandemic.